Adiposity Related Brain Plasticity Induced by Bariatric Surgery - Rullmann, Michael; Preusser, Sven; Poppitz, Sindy; Heba, Stefanie; Gousias, Konstantinos; Hoyer, Jana; Schütz, Tatjana; Dietrich, Arne; Müller, Karsten; Hankir, Mohammed K.; Pleger, Burkhard (Frontiers in Human Neuroscience, 2019)
Previous MRI studies revealed structural-functional brain reorganization twelve months after gastric-bypass surgery, encompassing cortical and subcortical regions of all brain lobes as well as the cerebellum. Changes in the mean of cluster-wise gray/white matter density (GMD/WMD) were correlated with the individual loss of body mass index (BMI), rendering the BMI a potential marker of widespread surgery-induced brain plasticity. Here, we investigated voxel-by-voxel associations between surgery-induced changes in adiposity, metabolism and inflammation and markers of functional and structural neural plasticity. We re-visited the data of patients who underwent functional and structural magnetic resonance imaging, six months (n=27) and twelve months after surgery (n=22), and computed voxel-wise regression analyses. Only the surgery-induced weight loss was significantly associated with brain plasticity, and this only for GMD changes. After six months, weight loss overlapped with altered GMD in the hypothalamus, the brain’s homeostatic control site, the lateral orbitofrontal cortex, assumed to host reward and gustatory processes, as well as abdominal representations in somatosensory cortex. After twelve months, weight loss scaled with GMD changes in right cerebellar lobule VII, involved in language-related/cognitive processes, and, by trend, with the striatum, assumed to underpin (food) reward. These findings suggest time-dependent and weight-loss related gray matter plasticity in brain regions involved in the control of eating, sensory processing and cognitive functioning.